Medical Student Core Clinical Ultrasound Milestones: A Consensus Among Directors in the United States. (18th January 2016) - Dinh, Vi Am; Lakoff, Daniel; Hess, Jamie; Bahner, David P.; Hoppmann, Richard; Blaivas, Michael; Pellerito, John S.; Abuhamad, Alfred; Khandelwal, Sorabh
Abstract : Objectives: Many medical schools are implementing point‐of‐care ultrasound in their curricula to help augment teaching of the physical examination, anatomy, and ultimately clinical management. However, point‐of‐care ultrasound milestones for medical students remain unknown. The purpose of this study was to formulate a consensus on core medical student clinical point‐of‐care ultrasound milestones across allopathic and osteopathic medical schools in the United States. Directors who are leading the integration of ultrasound in medical education (USMED) at their respective institutions were surveyed. Methods: An initial list of 205 potential clinical ultrasound milestones was developed through a literature review. An expert panel consisting of 34 USMED directors across the United States was used to produce consensus on clinical ultrasound milestones through 2 rounds of a modified Delphi technique, an established anonymous process to obtain consensus through multiple rounds of quantitative questionnaires. Results: There was a 100% response rate from the 34 USMED directors in both rounds 1 and 2 of the modified Delphi protocol. After the first round, 2 milestones were revised to improve clarity, and 9 were added on the basis of comments from the USMED directors, resulting in 214 milestones forwarded to round 2. After the second round, only 90 milestones were found to have a high level of agreement and were included in the final medical student core clinical ultrasound milestones. Conclusions: This study established 90 core clinical milestones that all graduating medical students should obtain before graduation, based on consensus from 34 USMED directors. These core milestones can serve as a guide for curriculum deans who are initiating ultrasound curricula at their institutions. The exact method of implementation and competency assessment needs further investigation.